Global measure of electricity security: A composite index approach - Neelawela, U.D.; Selvanathan, E.A.; Wagner, Liam (2019)
Electricity lies at the heart of eliminating poverty and developing the world into a safe, equitable and environmentally sustainable place. While modern society depends on the provision of reliable and affordable electricity supplies, increasing demand for electricity and supply constraints have created a massive challenge to the world's electricity security. Until now, no framework has been built to evaluate electricity security that can be applied globally. Therefore, the aim of this paper is to develop a global index which can measure the electricity security of a country without being restricted to their resource endowment, economic development, geographic area, generation mix, or population density. We identified a series of unique indicators which represent the dimensions of electricity security. Then a composite index was developed by aggregating the indicators and it quantifies the electricity security status of each country allowing us to rank them based on their performance. To test the index we used data for 14 countries over a period of 25 years. The validity of the index is assessed by the results, which order countries in a logical way and also captures past incidents that have affected their respective power sectors. Reasons for weak performances of electricity sectors and the policies to overcome those issues for a sustainable electricity industry were also identified.